2018
DOI: 10.1007/s10916-018-1029-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Periventricular Leukomalacia in Neonates after Cardiac Surgery Using Machine Learning Algorithms

Abstract: Periventricular leukomalacia (PVL) is brain injury that develops commonly in neonates after cardiac surgery. Earlier identification of patients who are at higher risk for PVL may improve clinicians' ability to optimize care for these challenging patients. The aim of this study was to apply machine learning algorithms and wavelet analysis to vital sign and laboratory data obtained from neonates immediately after cardiac surgery to predict PVL occurrence. We analyzed physiological data of patients with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Jalali at el. 23 also found that ML algorithms and wavelet analysis can be accurately applied to prediction models to assess the occurrence of periventricular leukomalacia in neonates postcardiac surgery. Artificial neural networks (ANNs) nonlinear technology are equally useful in identifying risk factors and predicting mortality in patients who have undergone cardiac surgery.…”
Section: Technology and Cardiac Surgerymentioning
confidence: 94%
See 1 more Smart Citation
“…Jalali at el. 23 also found that ML algorithms and wavelet analysis can be accurately applied to prediction models to assess the occurrence of periventricular leukomalacia in neonates postcardiac surgery. Artificial neural networks (ANNs) nonlinear technology are equally useful in identifying risk factors and predicting mortality in patients who have undergone cardiac surgery.…”
Section: Technology and Cardiac Surgerymentioning
confidence: 94%
“…Both Saeyeldin et al 21 and Ruiz‐Fernández et al 22 highlight the same message that information from AI about risks allows anticipation of treatment plans, overall significantly contributing to clinical decisions. Jalali at el 23 . also found that ML algorithms and wavelet analysis can be accurately applied to prediction models to assess the occurrence of periventricular leukomalacia in neonates postcardiac surgery.…”
Section: Technology and Cardiac Surgerymentioning
confidence: 98%
“…Given the preoperative characteristics of a patient, one can follow the decision "path" along the branches of the tree, understanding at each step the sequential decisions taken, and also comprehend the characteristics of resulting patient cohorts with similar risk, as revealed by the tree's terminal leaves. The ability to understand the decisions of the OCT algorithm is in advantageous contrast with findings of various studies in similar settings showing the use of "black-box" deep learning solutions, [21][22][23][24][25][26][27] which, despite higher performance indicators, have architectural inner workings which are obscure not just for clinicians, but for AI experts as well. Such black-box methods cannot provide interpretable explanations of "why" a given patient is assigned a certain outcome risk.…”
Section: Commentmentioning
confidence: 99%
“…Table 1 summarizes and shows the characteristics of the studies. Fourteen studies evaluated the functionality of CDSSs in ICUs [51][52][53][54][55][56][57][58][59][60][61][62][63][64], three examined the applicability of databases in ICUs [65][66][67], one studied investigated the usefulness of EHRs [68], and another one considered CPOE [69]. Lastly, three analyzed the function of combinations of CDSS/CPOE and CDSS/EHR [70][71][72].…”
Section: Study Characteristicsmentioning
confidence: 99%